Long-term effects of orthognathic surgery on masticatory function in individuals with cleft lip and palate: A prospective study - Patricia Martins Bueno; Paulo Alceu Kiemle Trindade; Laís Hollara Medeiros; Leide Vilma Fidélis da Silva; Ivy Kiemle Trindade-Suedam (Journal of Oral Biology and Craniofacial Research)
Objective: To prospectively evaluate the long-term effects of orthognathic surgery on masticatory function in individuals with repaired complete cleft lip and palate and to compare the results with a control group. Material and methods: A total of 40 individuals were prospectively analyzed before (PRE-ORTHOG) and approximately 12 months after orthognathic surgery (POST-ORTHOG). The participants were divided into two groups: 1) Cleft Lip and Palate Group (CLP): 20 adults with CLP undergoing orthognathic surgery (14 ♂, 6 ♀, age 24 ± 3 years), and 2) Control Group (CON): 20 paired adults with Angle Class I skeletal pattern who had never undergone orthognathic surgery (14 ♂, 6 ♀, age 25 ± 5 years). Three variables were evaluated: 1) Bite Force (BF) (measured in Newtons – N) presented as the average of the bite force from the right and left molars (x‾ RM + LM), using a gnathodynamometer (IDDK Kratos), 2) Masticatory Efficiency (ME) (ranging from 0 to 1, with values closer to 1 indicating poorer efficiency), assessed through a dual-color masticatory gum test analyzed visually and optoelectronically (ViewGum©), and 3) Masticatory Capacity (MC): patient-reported ability to chew, rated on a two-point scale (P/R = poor to reasonable, G/O = good to optimal). Results: In the PRE-ORTHOG phase, the BF for the CLP group (x‾ RM + LM = 285 ± 141) was significantly lower compared to the CON group (x‾ RM + LM = 524 ± 202). In the POST-ORTHOG phase, the CLP group (x‾ RM + LM = 373 ± 129) showed significant improvements in BF in relation to the PRE-ORTHOG phase, with values similar to those of the CON group. Masticatory efficiency improved significantly in the POST-ORTHOG phase (0.222 ± 0.071) compared to PRE-ORTHOG (0.470 ± 0.126) in the CLP group, while PRE-ORTHOG values were worse than those of the CON group (0.148 ± 0.050). Furthermore, 45 % of CLP participants reported P/R MC before surgery, while none reported this after surgery, a statistically significant improvement. The POST-ORTHOG MC results for CLP participants were comparable to the CON group, with 100 % reporting G/O MC after surgery. Conclusions: Overall, the group with CLP demonstrated impaired masticatory function in the preoperative phase compared to the control group across all variables analyzed. Orthognathic surgery improves masticatory function in patients with CLP, with postoperative parameters comparable to those of the control group.